2024
DOI: 10.1002/adma.202312348
|View full text |Cite
|
Sign up to set email alerts
|

Exploring and Engineering 2D Transition Metal Dichalcogenides toward Ultimate SERS Performance

Xiao Tang,
Qi Hao,
Xiangyu Hou
et al.

Abstract: Surface‐enhanced Raman spectroscopy (SERS) is an ultrasensitive surface analysis technique that is widely used in chemical sensing, bioanalysis, and environmental monitoring. The design of the SERS substrates is crucial for obtaining high‐quality SERS signals. Recently, two‐dimensional transition metal dichalcogenides (2D TMDs) have emerged as high‐performance SERS substrates due to their superior stability, ease of fabrication, biocompatibility, controllable doping, and tunable bandgaps and excitons. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 146 publications
0
2
0
Order By: Relevance
“…Recent studies have shown that defect engineering can provide additional charge transfer pathways, thereby improving the SERS activity. 7–9 However, it is experimentally difficult to achieve suitable band edge positions and suitable band gaps by defect engineering, resulting in limited band structure manipulation capability and molecular selectivity. Consequently, formulating a novel approach to reliably and efficiently boost the EF remains a crucial challenge for SERS.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that defect engineering can provide additional charge transfer pathways, thereby improving the SERS activity. 7–9 However, it is experimentally difficult to achieve suitable band edge positions and suitable band gaps by defect engineering, resulting in limited band structure manipulation capability and molecular selectivity. Consequently, formulating a novel approach to reliably and efficiently boost the EF remains a crucial challenge for SERS.…”
Section: Introductionmentioning
confidence: 99%
“…Surface-enhanced Raman scattering (SERS) stands as a powerful spectroscopic method that notably amplifies the Raman signals of molecules on roughened noble metal substrates, providing significant insights into molecular structures and their interactions. The remarkable sensitivity of SERS, which reaches the capability of detecting single molecules, is derived from two fundamental mechanisms: the electromagnetic mechanism (EM) and chemical mechanism (CM) . EM enhancement primarily emerges from the localized surface plasmon resonance (LSPR) in metallic nanostructures, significantly intensifying electromagnetic fields at the surface around the materials. , Conversely, CM enhancement is a consequence of charge transfer (CT) interactions between the adsorbed molecules and the substrate, which modifies the polarizability of the molecules, thereby affecting their Raman scattering cross sections. …”
mentioning
confidence: 99%